The effect of foreign direct investment on structural transformation in developing countries - Ezo Emako; Seid Nuru; Mesfin Menza (Cogent Economics & Finance, 2022)
This paper investigates the effects of foreign direct investment (FDI) on structural transformation using panel data from 44 developing countries and four newly industrialized countries from 1990 to 2018 by employing the generalized method of moment approach of Arellano-Bond (1991). The estimated results suggest that FDI inflows have a positive significant effect on the structural transformation. In addition, the paper explores the channels through which FDI affects structural transformation. The Principal Component Analysis (PCA) indicates that structural change contributes 55.95 percent to structural transformation, followed by capital accumulation (37.92 percent) and economic growth (6.13 percent). Particularly, manufacturing and service-sector output and employment growth, as well as urbanization, are major pathways via which FDI fosters structural transformation in developing countries. Therefore, special consideration should be given to FDI motivated by manufacturing exports, as well as policies that boost absorption capacity and enable labor mobility in developing countries.
Keywords: 330; foreign direct investment; structural transformation; structural change; economic growth; developing countries